The future of digital data, heritage and curation in a more-than human world - Cameron, Fiona 1960- (Routledge, Taylor & Francis Group, 2021)
"The Future of Digital Data, Heritage and Curation in a More-than Human World critiques digital cultural heritage concepts, their application to data and develops new theories, curatorial practices and a more-than human museology for a contemporary and future world. Presenting a diverse range of case examples from around the globe, Cameron offers a critical and philosophical reflection on the ways in which digital cultural heritage is currently framed as societal data worth passing on to future generations in two distinct forms: digitally born and digitizations. Demonstrating that most perceptions of digital cultural heritage are distinctly western in nature, the book also examines the complicity of such heritage in climate change and environmental destruction and injustice. Going further still, the book theorizes the future of digital data, heritage, curation and the notion of the human in the context of the profusion of new types of societal data and production processes driven by the intensification of data economies and through the emergence of new technologies. In so doing, the book makes a case for the development of new types of heritage that comprise AI, automated systems, biological entities, infrastructures, minerals and chemicals - all of which have their own forms of agency, intelligence and cognition. The Future of Digital Data, Heritage and Curation is essential reading for academics and students engaged in the study of museums, archives, libraries, galleries, archaeology, cultural heritage management, information management, curatorial studies and digital humanities"
Der Anfang des Sachtitels (The future of digital data, heritage and curation) ist typographisch hervorgehoben
Literaturangaben
Keywords: Kulturerbe; Digitalisierung; Digitale Daten; Kulturgut; Data curation; Digital preservation; Cultural property / Protection; Museums / Curatorship; Museum information networks